Fabrication of Low-Density Shock-Propagation Targets Using Two-Photon Polymerization. (17th February 2018) - Stein, O.; Liu, Y.; Streit, J.; Campbell, J. H.; Lu, Y. F.; Aglitskiy, Y.; Petta, N.
Abstract: Low-density foam targets were fabricated by direct laser writing using two-photon polymerization (2PP). The targets were used in high-energy-density shock-propagation experiments carried out on the NIKE laser system at the Naval Research Laboratory (NRL). The basic target comprised a rectilinear foam rod with a log-pile-like microstructure with overall dimensions of 2000 × 250 × 315  μ m 3 and a nominal density of ~100 mg/cm 3 . The foam block is topped with a 15- μ m-thick, full-density ablation layer that is integrated into the 2PP printing process. The main challenge in fabricating the foam targets comes in maintaining dimensional and structural stability during 2PP postprocessing particularly during development, drying, and release from the substrate. Twelve 2PP foam rods were characterized and then built into targets. The characterization data show shrinkage of ~5% to 15% in overall dimensions attributed mainly to shrinkage of the acrylic resin (IP-Dip). Continuing development shows that use of the more stable IP-S commercial resin leads to significantly improved foam structure stability, reduced shrinkage, and a lower number of inherently weak stitching boundaries. The 12 targets provided to NRL have been shot; an example of the type of data obtained is presented.